2018
DOI: 10.1098/rstb.2018.0013
|View full text |Cite
|
Sign up to set email alerts
|

Are sulfate effects in the mayfly Neocloeon triangulifer driven by the cost of ion regulation?

Abstract: Elevated major ion concentrations in streams are commonly observed as a consequence of resource extraction, de-icing and other anthropogenic activities. Ecologists report biodiversity losses associated with increasing salinity, with mayflies typically being highly responsive to increases of different major ions. In this study, we evaluated the performance of the mayfly Neocloeon triangulifer reared for its entire larval phase in a gradient of sulfate concentrations. Two natural waters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
3
27
1
Order By: Relevance
“…The elevated concentrations of major ions in simulated Powell River water caused a significant reduction in metrics related to energy storage in adult L. fasciola, in contrast to results of a previous study in our laboratory, which showed no significant effect of this water on growth of juvenile Villosa iris (Ciparis et al 2015). Food availability may affect the response of freshwater invertebrates to the energetic demands of salinity stress; individuals with optimal nutrition may be less sensitive compared to individuals with suboptimal nutrition (Buchwalter et al 2018). The ratio of food availability to energy demands may have been greater for juvenile V. iris, because the feeding rate used in Ciparis et al (2015) was optimized to promote mussel growth.…”
Section: Cwcscontrasting
confidence: 77%
See 2 more Smart Citations
“…The elevated concentrations of major ions in simulated Powell River water caused a significant reduction in metrics related to energy storage in adult L. fasciola, in contrast to results of a previous study in our laboratory, which showed no significant effect of this water on growth of juvenile Villosa iris (Ciparis et al 2015). Food availability may affect the response of freshwater invertebrates to the energetic demands of salinity stress; individuals with optimal nutrition may be less sensitive compared to individuals with suboptimal nutrition (Buchwalter et al 2018). The ratio of food availability to energy demands may have been greater for juvenile V. iris, because the feeding rate used in Ciparis et al (2015) was optimized to promote mussel growth.…”
Section: Cwcscontrasting
confidence: 77%
“…When exposed to elevated SO 4 2À concentrations, mayflies take up SO 4 2À rapidly (Scheibener et al 2017); freshwater mussels take up SO 4 2À more slowly, but the concentration in the hemolymph eventually becomes isoionic with the exposure water (Dietz et al 2000). Mayflies exposed to elevated concentrations of SO 4 2À had reduced time to emergence, attributed to the energetic cost of active SO 4 2À excretion (Buchwalter et al 2018). There also may be an energetic cost of SO 4 2À excretion in freshwater mussels, as both freshwater mussels and mayflies appear to transport SO 4 2À using anion exchange (Dietz et al 2000;Buchwalter et al 2018).…”
Section: Cwcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake of SO 2À 4 in five mayfly species (including Maccaffertium sp.) increased with increasing external SO 2À 4 concentration, but unlike Na þ , saturation of SO 2À 4 was observed ( [30]; see also from this issue Buchwalter et al [49]). That is, the rate of increase in SO 2À 4 uptake decreased with increasing external SO 2À 4 concentration.…”
Section: Hypothesis 1-energetics Of Ion Uptakementioning
confidence: 87%
“…This could be related with the increase in the uptake of ions, loss of pH regulation or Na poisoning, which requires testing in future studies. Also, Buchwalter et al [62] show that elevated SO 4 2 -, rather than causing a loss of SO demand associated with maintaining homeostasis that is manifested primarily in reduced growth rates and associated developmental delays. They also identify two genes related to SO 4 22 transport in this species, which may be a promising tool for investigating mechanisms of sulfate toxicity.…”
Section: (B) What Are the Physiological Effects Of Freshwater Salinizmentioning
confidence: 99%